Disruption of white matter integrity and its relationship with cognitive function in non-severe traumatic brain injury - Aimi Nadhiah Abdullah; Asma Hayati Ahmad; Rahimah Zakaria; Sofina Tamam; Aini Ismafairus Abd Hamid; Wen Jia Chai; Hazim Omar; Muhammad Riddha Abdul Rahman; Diana Noma Fitzrol; Zamzuri Idris; Abdul Rahman Izaini Ghani; Wan Nor Azlen Wan Mohamad; et al. (Frontiers, 2024)
Indexed by WOS/Scopus/ERA